1985
DOI: 10.1139/v85-572
|View full text |Cite
|
Sign up to set email alerts
|

Étude statistique des effets de solvant. III. Calcul et interprétation de paramètres empiriques de polarité à partir de propriétés physicochimiques des solvants purs

Abstract: 3492 (1985) Using multivariational statistical methods, the calculation and interpretation of empirical parameters of the polarity of solvents has been reexamined. The size of the sample used (57 aprotic solvents and 24 protic solvents) assures that it is representative. For each solvent, the data tabulated include some physical constants (dielectric constants, dipole moments, refractive indices, molar refractions, boiling points, Hildebrand's 6 parameters) or theoretical values (energy levels of frontier or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…[21][22][23][24] The 138 sustainable solvents have been listed through the review of academic and technical literature (see Table 2). These solvents have been used as supplementary solvents and have been positioned in the classification established with the 153 traditional solvents.…”
Section: Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] The 138 sustainable solvents have been listed through the review of academic and technical literature (see Table 2). These solvents have been used as supplementary solvents and have been positioned in the classification established with the 153 traditional solvents.…”
Section: Data Setmentioning
confidence: 99%
“…The base dataset is constituted by the 153 organic solvents proposed by Gramatica et al 20 as an extension of Chastrette's classification. [21][22][23][24] The 138 sustainable solvents have been listed through the review of academic and technical literature (see Table 2). These solvents have been used as supplementary solvents and have been positioned in the classification established with the 153 traditional solvents.…”
Section: Data Setmentioning
confidence: 99%
“…Another option for treating this type of dimensionality and interrelation questions is the conventional PCA. Chastrette and Carretto applied PCA to analyze 231 and to calculate empirical parameters of solvent polarity starting with the physicochemical properties of the solvents; 232 Chastrette and coworkers 233 used multivariate statistical treatment to classify 83 solvents using eight solvent parameters (K, MR, δ, µ, n D , bp, H , and L ), but their focus was mainly on the grouping of solvents rather than solvent scales. Nevertheless, from the intercorrelation of the solvent parameters they concluded that fewer than eight parameters should be sufficient to describe the whole dimensionality.…”
Section: Principal Component Analysis (Pca) Approachmentioning
confidence: 99%
“…26 Additionally, besides being more polar, the diol function is less pH-dependant than a carboxylic acid function; the pK a value is 4.76 for acetic acid, whereas it is over 14 for ethylene glycol (14.22). 25 The diol-modified porous silicon surface presented in this work is expected not to be modified when exposed to varying environmental pH conditions. Such hydrophilic and inert-to-pH-change surfaces can be useful in biological and biosensing applications, where hydrophilic stable surfaces are desirable in various buffered conditions.…”
mentioning
confidence: 94%
“…This is explained by the higher polarity of a diol function compared to that of a carboxylic acid function, as attested by the values of the dipole moments for ethylene glycol (m = 7.61) compared to acetic acid (m = 5.6). 25 The polarity of solvents is also known to be linked to their dielectric constant, which is 37 and 6.1 for ethylene glycol and acetic acid, respectively. 26 Additionally, besides being more polar, the diol function is less pH-dependant than a carboxylic acid function; the pK a value is 4.76 for acetic acid, whereas it is over 14 for ethylene glycol (14.22).…”
mentioning
confidence: 99%